The 2012 french presidential elections the inevitable alternation - Evans, Jocelyn; Ivaldi, Gilles; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Was the victory of François Hollande, the Socialist challenger to Nicolas Sarkozy, inevitable in the 2012 French Presidential elections? This book argues that a combination of economic downturn, policy choices and personal unpopularity meant that the Right-wing incumbent faced an almost impossible task in holding onto power for another five years.
Keywords: Science; Science; Science, general